IMPROVING STUDENT MOTIVATION TO INTRODUCE THE BENEFITS OF INTERNET AT ELEMENTARY SCHOOL LEVEL AT THE TEBET INDONESIAN ORPHANAGE DORMITORY - Rima Tamara Aldisa; Frenda Farahdinna (International Journal of Teaching and Learning, 2024)
In this era, the level of progress is increasing with increasingly fierce competition. Every day, week to month there are more and more new scientific creations, technological developments that are entering the field of human life. One example of technology, namely in the world of the internet. This technology has become a friend of human life at this time and era. Every day, most people do activities with him. Therefore, we carry out training activities to increase motivation for elementary school children in orphanages regarding understanding of the internet world. The target of this activity is children at elementary school level to be able to understand the positive and negative impacts of the internet world today. Student in orphanages need technology and knowledge to gain new knowledge, at least an introduction to what a computer is and what it is. what is the internet, how to use the internet, the good and bad impacts of the internet, and many more. This is aimed at introducing student to internet technology well so that later they can adapt easily when there are lessons.